Medical Diagnoses in a University Athlete Training Room Clinic. Issue 1 (January 2022) - McMurray, Nathan; Reinke, Emily; Riboh, Jonathan; Pyles, Courtney; Bytomski, Jeffrey
Abstract : Introduction: Approximately 560 000 student–athletes participate in university athletic programs every year. These athletes develop a variety of medical injuries and illnesses during their time at the university. There is currently a paucity of data with regarding medical encounters in a dedicated university athlete training room clinic. Objective: This study aims to provide data regarding medical diagnoses from a university athlete training room clinic. Study design: Descriptive epidemiology study. Setting: University athlete training room clinic. Patients: University athletes. Methods: The electronic medical record for a year-round, athlete-only training room clinic at a private US university was reviewed. Athlete age, sex, sport, date of medical encounter, and encounter diagnoses across 5 calendar years were recorded; medical diagnoses were then manually stratified into diagnostic categories and subgroups. Results: A total of 1258 university athletes were evaluated during 5303 medical encounters. Approximately two-thirds of athletes were evaluated one or more times per year. Average number of encounters per athlete per year was 2.2 (0.6-3.8, 95% confidence interval). The football team accounted for the greatest number of encounters (15.2% of total encounters). The most common medical diagnosis category was otorhinolaryngology (30.6% of total diagnoses). The most common diagnosis subgroup was upper respiratory infection (14.8% of total diagnoses). Conclusions: Approximately two-thirds of athletes were evaluated annually with an average of 2 encounters per athlete per year. Upper respiratory infection represented the most common individual diagnosis. The results reported in this study may be useful in directing future care and research of university athletes. Abstract : Supplemental Digital Content is Available in the Text.